Effect of Combining Electron Beam Irradiation and Alkaline Pretreatments of OPEFB for Enzymatic Hydrolysis and Fermentation of Ethanol - Deliana Dahnum; Vera Barlianti; Kiky C. Sembiring; Anis Kristiani; Muryanto Muryanto; Yanni Sudiyani (Research Center for Chemistry - LIPI, 2017)
The effect of pretreatment process from the combination of electron beam irradiation and alkaline to Oil Palm Empty Fruit Bunch (OPEFB) was studied. The combination of pretreatment method was considered as an alternative way to increase glucose yield. In this study, OPEFB was pretreated using Electron Beam Irradiation (EBI) at 100 kGy and 300 kGy and followed by chemical pretreatment. In chemical pretreatment, irradiated OPEFB was reacted with sodium hydroxide 6% and 10% in stirred vessel at 4 bars and 150 oC for 30 min. The effectiveness of pretreatment was evaluated by calculating the composition of chemical component using National Renewable Energy Laboratory (NREL) Method. The samples which were hydrolyzed using enzymes with the addition of 30 FPU of Cellic®CTec2 per gram of pretreated biomass resulted high glucose in the amount of 9.86%. The fermentation process using Saccharomyces cereviceae obtained the highest ethanol concentration for 5.36% at 72h. The combination of the two pretreatment methods gave an effect on the weight loss, chemical composition, structure, and enzymatic hydrolysis product